(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
The purpose of the government’s rural revitalization is to use flexible market means to guide a large number of farmers (business entities) to participate in rural revitalization. Governments at all levels are the promoters, managers and supervisors of rural revitalization. Enterprises (cooperatives) participate in rural revitalization as organizers of farmers (operating entities), and are participants and organizers of rural revitalization. The government’s policies and support, and the number of farmers (operating entities) participating in rural revitalization are the key factors that affect the enthusiasm of enterprises (cooperatives) to participate in rural revitalization.